Global warming collaborative study on strategies to limit CO2 [carbon dioxide] emissions in Asia and Brazil - Bhandari, Preety; Pachauri, R. K.; Asian Energy Institute (New Delhi Tata McGraw-Hill Pub. Co., 1992)
Proceedings of a workshop held during Sept. 21-22, 1992 at New Delhi and organized by the Asian Energy Institute.
Keywords: Global warming -- Environmental aspects -- Asia -- Congresses; Carbon dioxide -- Environmental aspects -- Asia -- Congresses; Carbon dioxide -- Environmental aspects -- Brazil -- Congresses; Environmental policy -- Congresses; Global warming -- Environmental aspects -- Brazil -- Congresses; Power resources -- Environmental aspects -- Congresses